Permian trace fossils attributed to tetrapods (Tierberg Formation, Karoo Basin, South Africa) - van Dijk, D. E.; Channing, A.; van den Heever, J. A. (Bernard Price Institute for Palaeontological Research, 2002)
The discovery of a paving slab with a number of prints suggestive of footprints of tetrapods led to a reinvestigation of a trace fossil, known from three localities, of which only two photographs had been published, each with only four prints. The slab was traced to a previously unrecorded site, De Puts, near Calvinia, located in the Tierberg Formation of the Ecca Group of the Karoo Supergroup. The prints from all the sites are referred to Broomichnium permianum Kuhn 1958, of which Quadrispinichna parvia of Anderson 1974 is a synonym.
Main article
Keywords: Permian; trace fossils; tetrapod; Karoo